1995
DOI: 10.1128/iai.63.2.547-553.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mice immunized by primary vaginal Candida albicans infection develop acquired vaginal mucosal immunity

Abstract: It has been postulated that systemic cell-mediated immunity (CMI) is an important host defense mechanism against Candida infections of the vagina. However, in an estrogen-dependent murine model of experimental vaginal candidiasis, we recently showed that systemic Candida-specific Th1-type CMI induced by immunization with Candida culture filtrate antigen had no effect on vaginal Candida population levels during the course of a vaginal infection. In the present study, mice given a second vaginal inoculation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 31 publications
9
35
0
Order By: Relevance
“…Cell-mediated immune responses are believed to be critical for protection against oral candidiasis (10,17,42,46,59). Unlike vaginal candidiasis in which humoral immunity is believed to play a protective role (5,21,22), there are no obvious defects in the mucosal secretory IgA response of HIV-1-infected or AIDS patients that would account for the presence of oral candidiasis (13). Taken together with reports in the literature, our results suggest that cell-mediated immune function critical for protection against oral candidiasis is altered even before a marked decrease in CD4* T lymphocyte numbers is apparent in some HIV-1-seropositive women.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-mediated immune responses are believed to be critical for protection against oral candidiasis (10,17,42,46,59). Unlike vaginal candidiasis in which humoral immunity is believed to play a protective role (5,21,22), there are no obvious defects in the mucosal secretory IgA response of HIV-1-infected or AIDS patients that would account for the presence of oral candidiasis (13). Taken together with reports in the literature, our results suggest that cell-mediated immune function critical for protection against oral candidiasis is altered even before a marked decrease in CD4* T lymphocyte numbers is apparent in some HIV-1-seropositive women.…”
Section: Discussionmentioning
confidence: 99%
“…In both animal models, recovery from a primary infection provides protection against a subsequent infection. 28,29 Although this typically does not occur in women, the animal models may be useful to study anti-candidal immunity following vaccination (see below).…”
Section: Animal Models Versus Human Infectionmentioning
confidence: 99%
“…For experiments investigating the effects of circulating CD4 and CD8 cells on secondary vaginal infections, animals were first given a primary vaginal inoculation in the absence of estrogen treatment (4). At consecutive weeks following inoculation, randomly selected mice were monitored for DTH and vaginal fungal burden in order to establish that DTH had been induced and that the vaginal infection had cleared spontaneously as shown previously (4).…”
Section: Effects Of Systemic Circulating Cd4 and Cd8 T Cells On Seconmentioning
confidence: 99%
“…To study potential host defense mechanisms which provide protection against C. albicans vaginitis more closely, we used an estrogen-dependent murine model of experimental vaginal candidiasis. To date, our studies have shown (i) that a local vaginal C. albicans infection stimulates Candida-specific systemic Th1-type CMI (5,6), (ii) that preinduced Candidaspecific CMI expressed systemically does not protect mice against a vaginal C. albicans infection (7), (iii) that suppression of vaginal infection-induced Candida-specific delayed-type hypersensitivity (DTH) does not enhance the vaginal C. albicans burden (7), (iv) that the spontaneous resolution of a primary vaginal infection results in partial protection from a second vaginal infection, and (v) that this vaginal protection is retained when Candida-specific DTH is suppressed (4).…”
mentioning
confidence: 99%